Equilibrium Unemployment and Credit Market Imperfections: The Critical Role of Labour Mobility - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2002)
We investigate the interaction between labour and credit market imperfections for the determination of equilibrium unemployment within the framework of the right-tomanage approach. Our analysis highlights the critical role of labour mobility for the evaluation of the employment implications of intensified credit market competition. Without labour mobility increased bargaining power of banks will have adverse employment effects. However, with a labour force mobile across industries this relationship is frequently reversed if firms adopt profit sharing schemes. If employment at a fixed wage complements unemployment benefits to constitute the trade union's relevant outside option, intensified credit market competition will increase equilibrium unemployment. This relationship is shown to hold also for cases where the outside option incorporates profit sharing schemes as long as the labour market imperfections - measured by the relative bargaining power of the trade unions - are sufficiently strong.
Keywords: 330; wage and loan bargaining; compensation systems; equilibrium unemployment; outside options.